2019
DOI: 10.2175/106143017x15131012188295
|View full text |Cite
|
Sign up to set email alerts
|

Operational experience with a full‐scale anaerobic baffled reactor treating municipal wastewater

Abstract: The aim of the study was to investigate the influence of moderate temperatures on the efficiency of a full-scale anaerobic treatment system consisting of a primary sedimentation unit (PST) and an anaerobic baffled reactor (ABR, approx. 10 m 3 ). Therefore, two trials with different test setups in series were carried out (1st trial: continuous load; 2nd trial: diurnal variation load). The plant was fed with municipal wastewater and operated at temperatures between 8 and 24°C. The mean efficiency of the ABR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…The organic solids in wastewater come in contact with this sludge blanket in every compartment and get anaerobically degraded. The upflow movement of wastewater induces an interaction between biomass and substrate inside the compartments (Schalk et al 2019). The dynamic flow conditions maintain this sludge blanket either in packed, fluidized or expanded state.…”
Section: Introductionmentioning
confidence: 99%
“…The organic solids in wastewater come in contact with this sludge blanket in every compartment and get anaerobically degraded. The upflow movement of wastewater induces an interaction between biomass and substrate inside the compartments (Schalk et al 2019). The dynamic flow conditions maintain this sludge blanket either in packed, fluidized or expanded state.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were compared with those of Ayaz et al (2015), Hahn and Figueroa (2015), Schalk et al (2019), Saif et al (2021), andPfluger et al (2018) who reported the efficiency of pilot-scale or full-scale ABR under moderate-low temperatures and dynamic operating conditions. These references were included in Table 3.…”
Section: Operational Conditions and Treatment Efficiency At The Abr A...mentioning
confidence: 97%
“…Regarding the treatment of domestic or municipal wastewater, which is generally low-strength, COD removal efficiencies above 80% have been reported in the 25-35°C interval (Feng et al 2008;Nasr et al 2009). Other studies have been conducted at a wider range of temperatures varying from psychrophilic to mesophilic (Ayaz et al 2015;Feng et al 2008;Gomec 2010;Hahn and Figueroa 2015;Nasr et al 2009;Schalk et al 2019), reporting variable COD removal efficiencies from 43% to 84%. At low temperatures, the efficiency of ABRs is mainly attributed to the retention of particulate organic material within the ABR (Schalk et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of low‐cost substrates such as waste‐derived VFAs will reduce the cost of those terminal products. VFAs can also be used as carbon substrates to assist biological removal of nitrogen and phosphorus from wastewaters, resulting in higher nutrient removal efficiency compared to that using acetate (Schalk et al, 2019; Tong & Chen, 2007).…”
Section: Introductionmentioning
confidence: 99%